Militarized Cultural Encounters in the Long Nineteenth Century
XX, 370 p. 37 illus.
Keywords: This book explores European soldiers’ encounters with their continent’s exotic frontiers from the French Revolution to the First World War. In numerous military expeditions to Italy, Spain, Russia, Greece and the ‘Levant’ they found wild landscapes and strange societies inhabited by peoples who needed to be ‘civilized.’ Yet often they also discovered founding sites of Europe’s own ‘civilization’ (Rome, Jerusalem) or decaying reminders of ancient grandeur. The resulting encounters proved seminal in forging a military version of the ‘civilizing mission’ that shaped Europe’s image of itself as well as its relations with its own periphery during the long nineteenth century.